Odpowiedzi

2009-12-03T20:39:44+01:00
A)2z-2>0,5z+0,5
2z-0,5z>0,5+2
1,5z>2,5/:1,5
z>1,7

b)4y²-4y+1+7≤1+2y+y²+3y²
4y²-4y-2y-y²-3y²≤1-1-7
-6y≤-7/: (-6)
y≤7/6 <--(ułamek)

c)x√3 - 5x>1
i tak chyba zostawiamy
;)
2009-12-03T20:42:38+01:00
A) 2z - 1= 1/2 (z + 1)
2z - 1= 1/2z + 1/2
2z- 1/2z = 1/2 + 1
2z+ 1 1/2 I: 2
z= 3/2 : 2/1
z= 3/2 * 1/2
z = 3/4

b) 4y2 - 2 * 2y * 1 + 1 + 7 = 1 + 2 * 1 * y + y2 + 3y2
wszystkie kwadraty sie skrócą i wyjdzie :
-4y + 8 = 1 + 2y =
-4y - 2y = 1 - 8
-6y = -7I: ( -6 )
y= 7/6
y= 1 1/6

c ) x/3 - 5x = 1 I: ( /3 - 5 )
x= /3 - 5